Feminism's new age: gender, appropriation, and the afterlife of essentialism - Crowley, Karlyn (State University of New York Press, 2025)
Touched by an angel : the feminization of the new age in American culture -- The Indian way is what's inside : gender and the appropriation of American Indian religion in new age culture -- Gender on a plate : the calibration of identity in American macrobiotics -- The structure of prehistorical memory in the American goddess movement -- New age soul : the gendered coding of new age spirituality on the Oprah Winfrey show -- Conclusion : is new age culture the new feminism?